Rethinking Developmentally Appropriate Concept in Indonesian Picture Bible Story Book - Kartika B. Primasanti; Desi Yoanita (k@ta: A Biannual Publication on the Study of Languange and Literature, 2018)
In Christian education, inheriting faith values to children since a young age is a pivotal responsibility for parents, the church, and Christian education institutions. According to a previous study, inheriting these values is applied through the tradition of reading illustrated Bible together with parents. In this study, illustrated Bible is not the Bible. It is illustrated literature that contains Bible stories. Using the perspective of Developmentally-Appropriate, the researchers elaborated how illustrated Bible in the marketplace have or have not used the developmentally appropriate concept for young children. This research will be a reference to design illustrated Bible for young children, in the form of printed book or application, and a reference for parents and educators to choose an illustrated children Bible which is appropriate for a childâ€™s age, and for publishers to give age label for children Bible products. Keywords: children Bible, illustrated Bible, developmentally appropriate Â